HUBUNGAN STATUS GIZI SISWA DENGAN HASIL BELAJAR PENJASORKES PADA SISWA KELAS V SDN 010 BERINGIN JAYA KECAMATAN SENTAJO RAYA - Minas, Zulra; Agust, Kristi; ', Saripin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The problem in this research is learning outcome students are below a minimum learning competency standards (KKM) and the majority of the number of students is not far above the KKM. It may be caused by nutritional status possessed by the students. The purpose of this study was to determine the corelation of the nutritional status of students with the penjasorkes learning outcome students class V of SDN 010 Beringin Jaya District of Sentajo Raya. This research is correlational with a total sample of 35 people. Based on the research that has been conducted on class V SDN 010 Beringin Jaya District of Sentajo Raya obtained r = 0.514 medium category. Tests of significance using the formula t test Significance. From the calculation results are known t = 3.44, while t table = 1.679 so t = 3.44> t table = 1.679. That Hypothesis (Ho) rejected that reads: There is no significant corelation between the nutritional status of students (X) with the penjasorkes learning outcomes (Y). Based on the analysis of data obtained by the correlation coefficient of r = 0.514 where or significance was tested by t test and obtained t count equal to 3.44 means thitung> t table (1,679) thus Ha received, so it can be concluded there is a corelation the nutritional status of students with penjasorkes learning outcomes on class V SDN 010 Beringin Jaya District of Sentajo Raya.Keywords : Nutritional Status, Learning Outcome, Penjasorkes